Strategi Tunanetra X Berprestasi dalam Olahraga Catur Tingkat Internasional - Andika Firnanda; Fatmawati Fatmawati (Universitas Negeri Padang, 2019)
Starting from an X Blind who attended SLB A Payakumbuh. X went to school in a special school (SLB) but X also attended school in a regular school. The rest of the vision that is owned is used to read and act. When studying in a regular school, X is not accompanied by a special educator teacher (SET).None of the teachers who teach in this school has an extraordinary education background (PLB). However, Blind X was forced to move to SLB because of the parents' request that the child learn braille. This study uses a qualitative approach with descriptive research methods, focused on X-achiever X-blind strategies that will describe the conditions that occur as they were during the study. The subjects of this study were X-blind children. The process of collecting data in this study was carried out through interviews and documentation studies. The results of this study reveal the strategies of X Blindness achievement namely learning, self-confidence. Self-motivation as well as those that play a role for X Blind in achieving achievements.